Peran Kelompok Tani Dalam Meningkatkan Pemberdayaan Petani Kopi Kabupaten Probolinggo - Muhammad Yoga kurniawan; Hayatul Millah; Cici Widya Prasetyandari (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
This study aims to analyze the role of farmer groups in enhancing the empowerment of coffee farmers in Kalianan Village, Krucil Subdistrict, Probolinggo Regency. Empowerment is examined through three stages: Enabling (creating a conducive climate), Empowering (strengthening capacity), and Protecting (protecting farmers). The study uses a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. The results indicate that farmer groups significantly contribute to providing technical education, coffee processing training, and protection against market injustice and crop pests. Supporting factors include active farmer participation and village government support, while inhibiting factors involve farmers' lack of awareness and limited ongoing education. Overall, farmer groups play a positive role in increasing the independence and competitiveness of coffee farmers sustainably.